Stable oxygen isotopes in the Western Mediterranean during the Early-Middle Pleistocene transition - Maria Marino; Teresa Rodrigues; Ornella Quivelli; Angela Girone; Patrizia Maiorano; Franck Bassinot (PANGAEA, 2025)
Measurements of stable oxygen isotope analysis were performed on four to fifteen specimens of Globigerina bulloides (250–315 μm). These analyses were performed on an Isoprime 100 (Elementar) dual-inlet Isotope Ratio Mass Spectrometer (Elementar) at the Laboratoire des Sciences du Climat et de l extquotesingleEnvironnement (LSCE, France). The results are expressed as δ18O vs V-PDB (in extperthousand) through calibration to international NBS standards.
In: Marino, M et al. (2025): Paleoproductivity proxies and alkenone precursors in the Western Mediterranean during the Early-Middle Pleistocene transition [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.982519